Autotransplantation of surgically removed maxillary impacted canine, complications and prognosis - Mustafa, Naziyah Shaban; Hassan, Haszelini (Greenfort International Publisher, India, 2025)
Autotransplantation of surgically removed maxillary impacted canines is a practical treatment option for patients with impacted teeth, particularly when eruption of tooth is unbearable. This case study involves the surgical extraction of the impacted canine and its transplantation into a prepared socket in the right side of maxilla. While autotransplantation offers several advantages, including preservation of alveolar bone and natural aesthetics, it is associated with potential complications such as root resorption, ankylosis, pulp necrosis, and periodontal attachment loss.